Effect of resistance training with elements of stretching on body composition and quality of life in postmenopausal women - Socha, Małgorzata; Frączak, Paulina; Jonak, Wiesława; Sobiech, Krzysztof A. (Menopause Review/Przegląd Menopauzalny, 2016)
Introduction: Physical activity in elderly persons contributes to prevention and treatment of chronic disease and, through its influence on the musculoskeletal system, increases physical capability and improves mental function. Aim of the study was to assess the effect of resistance training with elements of stretching on body composition and quality of life in women of postmenopausal age. Material and methods : Thirty-eight postmenopausal women aged 62.5 ±5.8 years were randomly divided into two groups. One group participated in an 8-week training program (60 minutes, twice weekly; 4 MET [metabolic equivalent] 2 hours/week). The second group performed no training. A comparison was made of body composition and quality of life (SF-36 Health Survey) prior to and after 8 weeks of training. Results: In the training group, after 8 weeks there was a significant reduction in body fat (in %; p = 0.028), and an increase in fat-free mass (in %; p = 0.025) and total body water (in %; p = 0.021), which indicates increased muscle mass. Furthermore, there were statistically significant differences in the assessment of quality of life in physical (role-physical [RP], bodily pain [BP], general health [GH] scales; p < 0.005) and mental health (vitality [VT] scale; p = 0.05). In the non-exercising group no changes were observed in features examined in the initial and final test. Conclusions : Resistance training with elements of stretching in postmenopausal women improved body composition to achieve a reduction in risk factors associated with excess fatty tissue and muscle mass deficiency. It raises the quality of life in terms of both physical and mental function.